Spectra of superoxide-induced mutations in the lacI gene of a wild-type and a mutM strain of Escherichia coli K-12 - Ono, T; Negishi, K; Hayatsu, H (Mutation research, 1995)
We have analyzed the spectra of superoxide-induced mutations in the chromosomal lacI gene of a wild-type and a mutM strain of Escherichia coli K-12. The mutM strain is known to be deficient in removing 8-hydroxyguanine from DNA. An intracellular superoxide-generating agent, menadione, was used to cause the mutation. Analysis of the mutated DNA showed marked differences between the mutants from the wild type and those from the mutM strain. In the mutants from the wild type, all possible base-pair substitutions were present and their proportions were similar to each other, whereas in those from the mutM bacteria there was a 90% bias in favor of transversion. Furthermore, in the mutM strain GC-to-CG transversion rather than GC-to-TA was predominantly induced. 64% of the GC-to-CG transversions in the mutM strain occurred at the site of (CT/GC)GGC (mutated base underlined). The favorable mutation site, CTGGC, was the same as that of the UV- and sunlight-induced mutations previously reported: the mutations observed there were also G-to-C transversions. We speculate from these results that the superoxide in the cells may lead to production of a modified guanine that can pair with guanine and is subject to removal by the MutM protein.